PERSEPSI SISWA TENTANG PROSES PEMBELAJARAN SEJARAH DI SMA NEGERI 1 TELUK KERAMAT KABUPATEN SAMBAS - Rendi Rendi; Mashudi Mashudi; Agus Sastrawan Noor (Universitas Tanjungpura, 2022)
AbstractThis research aims to determine students perceptions about the process of learning in SMAN1 Teluk Keramat of Sambas Regency. The research method used descriptive method. Theresearch object was students of eleventh grade with 42 students. Data collection techniquesin this research used direct communication technique, indirect communication technique,and documentary study technique. Data collection tools used questionnaires, interviews, anddocumentations. The results of this research shows the teacher has carried out the historylearning process well. The student statements through a questionnaire that the learningobjectives carried out by the teacher are good, the learning material carried out by theteacher is good, the methods used by the teacher are good enough, the media used by theteacher is good, and the evaluation of learning carried out by the teacher has been good.This shows the history learning process at SMAN 1 Teluk Keramat of Sambas Regency isquite good.Keywords: Process of History Learning